STUDI KASUS LINGUISTIK FORENSIK: HOAKS REKAMAN SUARA YANG DIDUGA GATOT NURMANTYO - Saputro, Ghozali (Diksi, 2019)
(Title: A Forensic Linguistic Study Case: Hoax of Recorded Voice Who Was Allegedly From Gatot Nurmantyo). This study aimed to describe the comparison between languages on Gatot Nurmantyo's Similar Voice Sample (SVS) recording with language on Gatot Nurmantyo's Original Voice Sample (OVS) recordings. The data source were one SVS record and three OVS records (OVS01"”OVS03). Data were collected through observation, copying, and recording. The instrument for data collection was in the form of human, researcher himself with the recording devices and stationery. The analysis was carried out comprehensively with a review of various aspects including Phonology, Sociolinguistics, Discourse, and Stylistics. The results of the study were as follows. First, there were significant differences between languages on SVS and language on all three OVS recordings in terms of Sociolinguistic, Discourse and Stylistic aspects. Second, on the Phonological aspect there was a tendency for the similarities between language on the SVS recording and language on all three OVS recordings in several parts including the duration of word utterance, the energy intensity of the word utterance, and the sound of the words. Therefore, it could be concluded that on a Classical Likelihood Scales, the SVS and OVS recordings were not from the same speaker. Keywords: forensic linguistic, comprehensive, recording, Praat